Toward a Proto-Mande reconstruction and an etymological dictionary - (:unkn) unknown (My University, 2016)
Mande family includes more than 70 languages spoken in West Africa and is presumably one of the mid-range families of the Niger-Congo macrofamily. The current state of the Proto-Mande reconstruction is discussed in this paper: internal classification, phonological reconstruction (initial consonants, word-internal consonants, vowels, tones, metrical foot) and morphological reconstruction. The question of whether Mande belongs to the Niger-Congo macrofamily is also discussed.
Keywords: African Research